2009
DOI: 10.1371/journal.pgen.1000703
|View full text |Cite
|
Sign up to set email alerts
|

Dissection of the Complex Phenotype in Cuticular Mutants of Arabidopsis Reveals a Role of SERRATE as a Mediator

Abstract: Mutations in LACERATA (LCR), FIDDLEHEAD (FDH), and BODYGUARD (BDG) cause a complex developmental syndrome that is consistent with an important role for these Arabidopsis genes in cuticle biogenesis. The genesis of their pleiotropic phenotypes is, however, poorly understood. We provide evidence that neither distorted depositions of cutin, nor deficiencies in the chemical composition of cuticular lipids, account for these features, instead suggesting that the mutants alleviate the functional disorder of the cuti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
107
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(120 citation statements)
references
References 63 publications
(137 reference statements)
12
107
0
1
Order By: Relevance
“…The SEmediated splicing event is believed to prevent generation of related siRNAs to trigger posttranscriptional gene silencing . In addition, SE may also act as a transcription mediator (Voisin et al, 2009). By analysis of public tiling array data sets, we found that se-1, se-3, cbp20-1, and cbp80-285 indeed accumulated higher levels of pri-miRNAs compared with the wild type (see Supplemental Figure 14 online), confirming previous results (Laubinger et al, 2008).…”
Section: Se Cbp20 and Cbp80 Regulate Lincrna Biogenesissupporting
confidence: 87%
“…The SEmediated splicing event is believed to prevent generation of related siRNAs to trigger posttranscriptional gene silencing . In addition, SE may also act as a transcription mediator (Voisin et al, 2009). By analysis of public tiling array data sets, we found that se-1, se-3, cbp20-1, and cbp80-285 indeed accumulated higher levels of pri-miRNAs compared with the wild type (see Supplemental Figure 14 online), confirming previous results (Laubinger et al, 2008).…”
Section: Se Cbp20 and Cbp80 Regulate Lincrna Biogenesissupporting
confidence: 87%
“…The fusion zones are often marked by two adjacent polysaccharide cell walls with no visible cuticle separating the two organs, although the fused epidermal layers maintain their identity, as indicated by the differentiation of internal nonfunctional stomata within fusion zones (Sieber et al, 2000). In each of three Arabidopsis mutants exhibiting organ fusions, lacerata, bodyguard, and fiddlehead, ectopic organ fusions and cuticular permeability defects could be partially suppressed by a second mutation in SERRATE (Voisin et al, 2009). SERRATE is a C 2 H 2 zinc finger protein that is required for microRNA biogenesis, and hypomorphic alleles exhibit numerous developmental defects, including serrated leaf margins (Dong et al, 2008).…”
Section: The Cuticle and Developmentmentioning
confidence: 99%
“…In different accessions, the cuticle of the leaf blade is documented as a thin, electron-dense layer of 20-25 nm (Xiao et al, 2007;Voisin et al, 2009) (Figure 2A,D). A layered reticulate structure was observed at high magnification (Broun et al, 2004).…”
Section: The Ultrastructure Of the Cuticle In Rosette Leavesmentioning
confidence: 99%
“…It has been speculated that these structures represent residual cutinization in the absence of a distinct cuticle layer on the surface of the cell wall (Bessire et al, 2007;Li et al, 2007b) (Figure 2B,2C). Arabidopsis mutants that exhibit alterations in the composition of cutin in the leaves, such as the lacerata (lcr) (At2g45970) and bodyguard (bdg) (At1g64670) mutants, typically display visible modifications to the ultrastructure of the leaf cuticle (Kurdyukov et al, 2006a;Voisin et al, 2009). In the aberrant induction of type three genes 1 (att1) (At4g00360) mutant, the cuticle is broader and more electron-translucent than that of wt Arabidopsis (Xiao et al, 2004) (Figure 2E), while WAX INDUCER1/ SHINE1 (win1/shn1) (At1g15360)-overexpressing plants accumulate electron-dense material beneath a broad electron-translucent cuticle proper (Broun et al, 2004).…”
Section: The Ultrastructure Of the Cuticle In Rosette Leavesmentioning
confidence: 99%